Kolaboratif Pengelolaan Candi Borobudur dalam Penanggulangan Bencana Gunung Merapi - Pratikno, Hendro; Kurniadi, Anwar (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2021)
Mount Merapi is one of the most active volcanoes in Indonesia, which is administratively located in Sleman Regency and Magelang Regency in the Central Java Province. The Borobudur Heritage Conservation Center in Magelang Regency does not yet have a tandard Operating Procedure (SOP) for cleaning the temple from volcanic ash, and not clear who is the responsibe for it. If the condition is allowed, I could be bad impact on the safety and preservation aspects. The purpose of this study was to know how far the collaboration among stakeholder in managing of the Borobudur temple. This study usedqualitative research methods withdescriptive design. The results showed; 1) dialog among stakeholders didn’t find the solution; 2) buliding trust with making program Twin Villages espescially among villages that impacted by Merapi Mount eruption; 3) commitment to made program of structural anda non structural mitigation and also preparedness; 4) sharing understanding with making communication and collaboration and synergizing well patterned ; 5) temporary result of the distribution of authority was still not optimal so that it was impotant to make new official regulation. Theconclusian showed thecollaboration among stakeholders were still not optimal so it needed to make new offiscial regulation. Recomendation was to among manager stakeholders make it round table to determine new regulation on ministeri level as well as field level (Standard Operational Procedure/SOP).